Flexible Adipose‐Vascular Tissue Assembly Using Combinational 3D Printing for Volume‐Stable Soft Tissue Reconstruction. Issue 6 (25th November 2020) - Cho, Won‐Woo; Kim, Byoung Soo; Ahn, Minjun; Ryu, Yeon Hee; Ha, Dong‐Heon; Kong, Jeong Sik; Rhie, Jong‐Won; Cho, Dong‐Woo
Abstract: A new concept, assembling cell‐laden tissue modules, is for the first time proposed for soft tissue engineering. Adipose‐vascular tissue modules composed of a synthetic polymer‐based substructure and customized bioinks using planar 3D cell printing are engineered. Such tissue modules are systematically assembled into a synthetic polymer‐based module holder fabricated with rotational 3D printing, resulting in the development of a flexible and volumetric tissue assembly. Whereas most of the previous studies about the construction of adipose tissue are limited to hypoxia, poor vascularization, rapid resorption, and mismatch in mechanical properties, it is aimed to realize the construction of nonhypoxic, flexible, and volume‐stable tissue assembly in this study. The significance of engineered tissue assembly is proven through various in vitro and in vivo evaluations. In particular, stable volume and remarkable neovascularization/adipogenesis are observed in the implanted assembly over four weeks. Interestingly, the size of newly formed lipid droplets and the remodeled morphology in the assembly are comparable to those in native adipose tissue. As far as it is known, this work is a first report suggesting a cell printing‐based tissue assembly for functional reconstruction of soft tissue. Abstract : A new concept, assembling cell‐laden tissue modules, is for the first time proposed for engineering a flexible, volumetric, and functional adipose construct through combinational 3D printing.